2013
DOI: 10.1002/jgra.50269
|View full text |Cite
|
Sign up to set email alerts
|

Simulated ring current response during periods of dawn‐dusk oriented interplanetary magnetic field (By)

Abstract: [1] Ring current formation is mainly attributed to enhanced global magnetospheric convection and particle injection. One of the indicators of enhanced global magnetospheric convection is the transpolar potential. The transpolar potential has been shown to respond to dawn-dusk oriented interplanetary magnetic field (IMF), enhancing as the IMF magnitude grows. This suggests that the ring current should respond to dawn-dusk oriented IMF. This work examines the ring current response during periods of dawn-dusk ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…The arc formation and motion is affected by IMF B y as well. In addition, Mitchell et al [2013] showed that ring current, which is attributed to enhancing global magnetospheric convection, increases with increasing IMF B y magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The arc formation and motion is affected by IMF B y as well. In addition, Mitchell et al [2013] showed that ring current, which is attributed to enhancing global magnetospheric convection, increases with increasing IMF B y magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Although there exists many studies that show the importance of IMF Bz (e.g., Liemohn et al, 1999; Liemohn, Kozyra, Thomsen, et al, 2001) and the solar wind dynamic pressure (e.g., Shi et al, 2006) on the asymmetry of the ring current, the role of IMF By on ring current asymmetry has not been explored enough. There are very few studies on the effects of IMF By on ring current (e.g., Mitchell et al, 2013). Mitchell et al (2013) using simulation study suggested that the IMF By plays an important role in the ring current intensity as positive IMF By can increase the transpolar potential.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few studies on the effects of IMF By on ring current (e.g., Mitchell et al, 2013). Mitchell et al (2013) using simulation study suggested that the IMF By plays an important role in the ring current intensity as positive IMF By can increase the transpolar potential. However, they did not investigate the IMF By effects on ring current asymmetry.…”
Section: Introductionmentioning
confidence: 99%